Apathy is associated with critical psychological determinants of medication adherence in HIV disease - Babicz, Michelle A. (J Clin Psychol Med Settings, 2021)
Apathy is common in HIV, separable from depression, and has been associated with non-adherence to antiretroviral therapy (ART). We examined the associations between apathy and critical psychological determinants of ART adherence, per the Information-Motivation-Behavioral model, in 85 persons living with HIV. Apathy was measured using a composite of the apathy subscale of the Frontal Systems Behavioral Scale and the vigor-activation scale of the Profile of Mood States. Independent of major depressive disorder, apathy was related at small-to-medium effect sizes with motivation to adhere and self-efficacy for health-related decision making and medication management, but not with HIV knowledge or medication management skills. These findings suggest that apathy plays a unique role in several critical health adherence determinants and support the importance of assessment and management of apathy to maximize health outcomes among individuals with HIV disease.